Effects of melatonin and its analogues on neural stem cells. (15th January 2016) - Chu, Jiaqi; Tu, Yalin; Chen, Jingkao; Tan, Dunxian; Liu, Xingguo; Pi, Rongbiao
Abstract: Neural stem cells (NSCs) are multipotent cells which are capable of self-replication and differentiation into neurons, astrocytes or oligodendrocytes in the central nervous system (CNS). NSCs are found in two main regions in the adult brain: the subgranular zone (SGZ) in the hippocampal dentate gyrus (DG) and the subventricular zone (SVZ). The recent discovery of NSCs in the adult mammalian brain has fostered a plethora of translational and preclinical studies to investigate novel approaches for the therapy of neurodegenerative diseases. Melatonin is the major secretory product synthesized and secreted by the pineal gland and shows both a wide distribution within phylogenetically distant organisms from bacteria to humans and a great functional versatility. Recently, accumulated experimental evidence showed that melatonin plays an important role in NSCs, including its proliferation, differentiation and survival, which are modulated by many factors including MAPK/ERK signaling pathway, histone acetylation, neurotrophic factors, transcription factors, and apoptotic genes. The purpose of this review is to summarize the beneficial effects of melatonin on NSCs and further to discuss the potential usage of melatonin and its derivatives or analogues in the treatment of CNS neurodegenerative diseases. Highlights: Melatonin modulates cell fate of neural stem cells (NSCs). Melatonin modulates cell fate of NSCs via multiple mechanisms. Melatonin analogues or derivatives show good effects on NSCs. The multi-targeted compounds show therapeutic potential in Alzheimer's disease.